REVOLUTIONIZING M-COMMERCE - Naous, Hala (E-Journal VFU, 2024)
The number of people utilizing mobile devices is rising due to advancements in wireless technology, which also accelerates the growth of M-commerce through these devices. Mobile commerce is the new form of e-commerce that uses mobile terminals to perform transactions. Owing to its innate qualities of ubiquity, customization, adaptability, and distribution, mobile commerce offers companies previously unheard-of market potential as well as exceptional productivity and profitability. This paper presents an overview of mobile commerce development by examining the enabling technologies, the impact of mobile commerce on the business world, and the implications for mobile commerce providers. Explore the attitude towards adopting m-commerce in Lebanon.
Keywords: ECommerce; wireless technology; Business enterprises; Mobile Commerce